Antinociceptive and Anti-inflammatory Effects of Combined Administration of a-tocopherol and Diclofenac - Juaira, Tasneema; Begum, Noorzahan; Ali, Taskina (Journal of Bangladesh Society of Physiologist, 2015)
Background: Nonsteroidal anti-inflammatory drugs such as diclofenac are used for relief of pain and inflammation, but frequently cause gastrointestinal complications. This study aimed to explore that combination of diclofenac and ?-tocopherol (áT) are better analgesic as well as anti-inflammatory agent than that of diclofenac alone. Objective: To assess the effects of combination of diclofenac with á-tocopherol on pain and inflammation. Methods: This prospective experimental study was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka between January to December 2013. For this purpose, 15 male Long Evans rats were studied. On the basis of vitamin and drug administrations, the rats were divided into three (3) groups (5 rats in each). Control group received normal saline, one experimental group received diclofenac sodium (DS) at a dose of 10 mg/kg/body weight, and another experimental group received combination of DS with áT at a dose of 10 mg/kg/body weight and 500mg/kg/body weight, respectively. All the groups received single dose and equal volume (1 ml) through intraperitoneal route 1 hour before the test. Just one hour after administrations, they were subjected to formalin test followed by formalin induced paw edema test. The data were statistically analyzed by ANOVA followed by Bonferroni Post Hoc test. Results: Combined administration of DS and áT significantly (p<0.001) lowered the variables for nociceptive pain, central analgesic activity, inflammatory pain and inflammation than individual intervention of DS. Conclusion: From this study it may be concluded that, combined administration of diclofenac sodium and ±-tocopherol were more effective in lowering pain and inflammation than individual administration of diclofenac. Bangladesh Soc Physiol. 2015, June; 10(1): 30-35